Windwitch - Taylor, Laini (Taylor, Laini. Fairies of Dreamdark., 2025)
"For centuries faeries have lived safely in their ancient forests, but now their peace is under threat. Devils are escaping the prisons that have held them since the Dawn Days, and only one faerie stands in their way. Magpie Windwitch is the greatest--the only--devil-hunter of the Age. Together with her trusted band of crows, she tracks down and recaptures these ravenous beasts that devour everything in their path. When the hunt leads them to the legendary forest of Dreamdark, Magpie finds herself outmatched. Facing the greatest foe her kind has ever known (not to mention an imposter queen, a disgusting imp, and a young faerie warrior as infuriating as he is brave), one thing is certain: If she's to save the world, she'll need all thehelp she can get."--